In vitro hemocompatibility and cytotoxicity study of poly(2‐methyl‐2‐oxazoline) for biomedical applications. Issue 8 (7th February 2013) - Bauer, Marius; Schroeder, Susann; Tauhardt, Lutz; Kempe, Kristian; Schubert, Ulrich S.; Fischer, Dagmar
Abstract Since poly(2‐methyl‐2‐oxazolines) (PMeOx) attract high attention for the potential use in drug delivery, cytotoxicity, and hemocompatibility of a set of PMeOxs with molar masses in the range from 2 to 20 kDa are systematically investigated under standardized conditions in terms of molar mass, concentration and time dependency. PMeOx polymers are well tolerated in red blood cell aggregation and hemolysis assays without any damaging effects even at high concentrations up to 80 mg/mL. Only in long term cytotoxicity tests PMeOx polymers moderately influence cell viability in a time, concentration, and molar mass dependent manner. Referring to these results it can be concluded that PEtOx could be promising nonionic hydrophilic polymers for many biomedical applications without any cyto‐ and hemotoxic effects at typically used therapeutic doses. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013